2009
DOI: 10.1007/s10549-009-0646-0
|View full text |Cite
|
Sign up to set email alerts
|

A study of the effects of the aromatase inhibitors anastrozole and letrozole on bone metabolism in postmenopausal women with estrogen receptor-positive breast cancer

Abstract: International audienceALIQUOT (Anastrozole vs. Letrozole, an Investigation of Quality Of Life and Tolerability) was a prospective, open-label, randomized pharmacodynamic study designed to assess the effects of aromatase inhibitors (AIs) on bone turnover in healthy postmenopausal women with estrogen receptor-positive breast cancer. Ninety-four patients were randomized to receive either 12 weeks of letrozole (2.5 mg;  = 42) followed by 12 weeks of anastrozole (1 mg), or 12 weeks of anastrozole (1 mg;  = 42) foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…However, the current analysis is in accordance with some studies, indicating that prior tamoxifen treatment profoundly increases the effects of AIs on bone turnover, resulting in a greater decrease in BMD (McCaig et al 2010). A possible explanation for this phenomenon is the rebound effect; unfortunately, the positive influence of tamoxifen not only ceases when tamoxifen therapy is finished (McCaig et al 2010) but also causes a marked bone loss when switching to AI. Moreover, tamoxifen is a standard treatment for perimenopausal women, but not for postmenopausal women.…”
Section: :4supporting
confidence: 90%
See 1 more Smart Citation
“…However, the current analysis is in accordance with some studies, indicating that prior tamoxifen treatment profoundly increases the effects of AIs on bone turnover, resulting in a greater decrease in BMD (McCaig et al 2010). A possible explanation for this phenomenon is the rebound effect; unfortunately, the positive influence of tamoxifen not only ceases when tamoxifen therapy is finished (McCaig et al 2010) but also causes a marked bone loss when switching to AI. Moreover, tamoxifen is a standard treatment for perimenopausal women, but not for postmenopausal women.…”
Section: :4supporting
confidence: 90%
“…There is compelling evidence for its beneficial effects, from reducing bone resorption and stimulating bone formation in postmenopausal breast cancer patients (Resch et al 1998). However, the current analysis is in accordance with some studies, indicating that prior tamoxifen treatment profoundly increases the effects of AIs on bone turnover, resulting in a greater decrease in BMD (McCaig et al 2010). A possible explanation for this phenomenon is the rebound effect; unfortunately, the positive influence of tamoxifen not only ceases when tamoxifen therapy is finished (McCaig et al 2010) but also causes a marked bone loss when switching to AI.…”
Section: :4supporting
confidence: 84%
“…The interruption of tamoxifen combined with the rapid fall in estrogen levels induced by the AI may promote an accelerated loss of BMD following the switch [7,23,24]. McCaig et al [25] reported that stopping tamoxifen and starting AIs results in a significantly greater increase in bone turnover compared with commencing AIs in tamoxifen-naive patients. The measurement of bone turnover biomarkers also showed that the effect of AIs occurs relatively rapidly after initiation of the treatment [9,24,[26][27][28][29].…”
Section: Annals Of Oncology Original Articlesmentioning
confidence: 99%
“…They have shown themselves to be superior to the previous tamoxifen in terms of the efficacy, safety and tolerability profile (5). One side effect of these three compounds, however, is a decrease in bone mineral density (BMD) and an increased risk of fracture (6)(7)(8)(9)(10). In fact, by blocking the conversion of androgens to estrogens in peripheral tissue, they have proven to suppress plasma and tissue estrogen level by > 98% in vivo.…”
Section: Introductionmentioning
confidence: 99%